Artikel Review Fitokimia : Efektivitas Maserasi Soxhletasi sebagai Metode Ekstraksi - Miftakhul Rokhmah; Amanda Rafina Modesty; Auliya Ika Putri; Salsabiila Wina Delia; Adelia Girlani Bria; Maria Delsiana Ndun; Elsa Tectona Zuliyanti; Renata Setya Agustin; Petrus Paulus Bria; A’Yunil Hisbiah; Ivan Charles S.Klau; Arista Wahyu Ningsih (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
The Soxhlet extraction method uses repeated heating and solvent circulation to separate substances from mixtures, producing more extract faster than maceration with less solvent. However, this method requires pure solvents and is not suitable for thermolabile compounds as they can be degraded by heat. Soxhlet extraction is more effective for limited quantities of dry and fine herbal materials. This method is widely used to extract phytochemical compounds such as flavonoids, tannins, and curcumin, and has potential in cosmetic raw materials, herbal medicines, and antioxidant products. Although it uses more energy, this technique is efficient and continuous. Modern innovations such as combining it with Ultrasonic Assisted Extraction (UAE) or environmentally friendly microextraction are expected to increase extraction efficiency while reducing the use of organic solvents. Modifications to Soxhlet, including automation and assistive technologies such as high pressure, ultrasound, and microwaves, open up opportunities for commercialization and further research with more optimal results and more practical operations. The modified Soxhlet is considered a “panacea” in extraction due to the significant performance improvements achieved.